Becoming oneself : Dimensions of 'bildung' and the facilitation of personality development - Schneider, Käthe (VS Verlag für Sozialwissenschaften, 2012)
The basic concern of the volume is to determine the preconditions of personality development and to show their significance and their perspectives for educational science and for pedagogical practice. First, these basic preconditions of becoming oneself are collected in a single volume and discussed in terms of their significance for science and for educational practice. In all fundamental dimensions are understood as precondition of becoming oneself. "Bildung" is here for the first time understood as the formation of the overall individual personality, which the OECD postulates to be the key qualification of the Twenty-first Century. From a pedagogical perspective, it is a matter of furthering the personality. It provides research with a new perspective, in that it makes the furthering of the overall personality the object of education. Dr. Käthe Schneider is occupants of the chair for adult education at the Universität Jena.